Pelatihan Pembuatan Media Pembelajaran Menggunakan Animasi Flash Bagi Guru Sekolah Dasar - Ahmad Yusuf; Muhammad Ilham Bakhtiar; Rahmah Kumullah; Khairunnisa`a Tayyibu (STKIP Andi Matappa, 2021)
This community service aims to provide skills for elementary school teachers in using the Flash graphic animation program to create learning media. With good and appropriate media, the delivery of material with special characteristics can be better absorbed by students. The domino effect that is aimed at the future of mastery of these skills so that students' understanding of the material given increases so that it becomes good raw input as well. The service activity consists of two stages, namely the first stage of socialization and the second stage of training. Socialization and training were attended by several teachers (classroom teachers), preferably 30 teachers who filled out a questionnaire distributed by the author. The training material is about the use of Flash animation software, in particular making animation about a process. The training was quite successful, all participants were able to make animation with basic techniques well and develop learning animation independently. In fact, some participants were able to design more complex animations. However, additional efforts are still needed to achieve optimal results because some participants have not been able to make them independently.